INFLUENCE OF THE RATIO OF CALCIUM OXIDE AND SILICA ON MINERALOGICAL AND PHASE CHANGES OF SINTER FROM LIMONITE ORE - Amel Zahirović; Amira Pašalić (Journal of Sustainable Technologies and Materials, 2025)
Improving the quality of iron ore sintering and adding specific components has positive effects on blast furnace productivity. Optimizing basicity in the blast furnace charge is one way to improve all indices of production processes. Adjusting basicity aims to achieve the formation of new phase compounds that are favourable for the metallurgical and mineralogical sinter properties. The chemical analyses are insufficient for controlling the phase transition of multicomponent systems, as it is necessary to know the structure of all constituents. For that reason, X-ray diffraction is used for identifying minerals in sinter. Also, the physico-mechanical properties of sinter are investigated. Based on experimental results, the optimal basicity of limonite ore from mine "Omarska" Prijedor is determined.